26=\(\frac{x+\left(x-5\right)}{2}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(3x^3-\frac{3}{2}x^2-x^3-\frac{1}{2}x+\frac{1}{2}x+2=2x^3-\frac{3}{2}x^2+2\)
\(2x^2-10x-3x-2x^2=26\)
-13x=26
x=-2
\(a,2x\left(x-5\right)-x\left(2x+3\right)=26\)
\(\Leftrightarrow2x^2-10x-2x^2-3x=26\)
\(\Leftrightarrow-13x=26\)
\(\Leftrightarrow x=-2\)
\(b,\left(3x^2-x+1\right)\left(x-1\right)+x^2\left(4-3x\right)=\frac{5}{2}\)
\(\Leftrightarrow3x^3-3x^2-x^2+x+x-1+4x^2-3x^3=\frac{5}{2}\)
\(\Leftrightarrow2x=\frac{7}{2}\)
\(\Leftrightarrow x=\frac{7}{4}\)
\(\left(x+\frac{1}{5}\right)^2+\frac{17}{25}=\frac{26}{25}\\ \left(x+\frac{1}{5}\right)^2=\frac{26}{25}-\frac{17}{25}\\ \left(x+\frac{1}{5}\right)^2=\frac{9}{25}\\ \left|\left(x+\frac{1}{5}\right)\right|=\frac{3}{5}\)
TH1: \(x=\frac{3}{5}-\frac{1}{5}\\ x=\frac{2}{5}\)
TH2: \(\left|\left(x+\frac{1}{5}\right)\right|=-\frac{3}{5}\\ x=-\frac{3}{5}-\frac{1}{5}\\ x=-\frac{4}{5}\)
\(a,\left(x+\frac{1}{5}\right)^2+\frac{17}{25}=\frac{26}{25}\)
\(\Rightarrow\left(x+\frac{1}{5}\right)^2=\frac{9}{25}\)
\(\Rightarrow\left(x+\frac{1}{5}\right)^2=\left(\frac{3}{5}\right)^2\)
\(\Rightarrow x+\frac{1}{5}=\frac{3}{5}\)
\(\Rightarrow x=\frac{2}{5}\)
\(b,-1\frac{5}{27}-\left(3x-\frac{7}{9}\right)^3=-\frac{24}{27}\)
\(\Rightarrow-\frac{32}{27}-\left(3x-\frac{7}{9}\right)^3=-\frac{24}{27}\)
\(\Rightarrow\left(3x-\frac{7}{9}\right)^3=-\frac{32}{27}+\frac{24}{27}\)
\(\Rightarrow\left(3x-\frac{7}{9}\right)^3=-\frac{8}{27}\)
\(\Rightarrow\left(3x-\frac{7}{9}\right)^3=\left(-\frac{2}{3}\right)^3\)
\(\Rightarrow3x-\frac{7}{9}=-\frac{2}{3}\)
\(\Rightarrow3x=-\frac{2}{3}+\frac{7}{9}\)
\(\Rightarrow3x=\frac{1}{9}\)
\(\Rightarrow x=\frac{1}{27}\)
\(c,\left(x+\frac{1}{2}\right)\left(\frac{2}{3}-2x\right)=0\)
\(\Rightarrow\) \(\left[\begin{array}{nghiempt}x+\frac{1}{2}=0\\\frac{2}{3}-2x=0\end{array}\right.\) \(\Rightarrow\) \(\left[\begin{array}{nghiempt}x=-\frac{1}{2}\\2x=\frac{2}{3}\end{array}\right.\) \(\Rightarrow\) \(\left[\begin{array}{nghiempt}x=-\frac{1}{2}\\x=\frac{1}{3}\end{array}\right.\)
a) Vì \(x^2\ge0;\left(y-\frac{1}{10}\right)^2\ge0\)
Mà theo đề bài: \(x^2+\left(y-\frac{1}{10}\right)^2=0\)
=> \(\begin{cases}x^2=0\\\left(y-\frac{1}{10}\right)^2=0\end{cases}\) => \(\begin{cases}x=0\\y-\frac{1}{10}=0\end{cases}\) => \(\begin{cases}x=0\\y=\frac{1}{10}\end{cases}\)
Vậy \(x=0;y=\frac{1}{10}\)
b) Vì \(\left(\frac{1}{2}x-5\right)^{26}\ge0;\left(y^2-\frac{1}{4}\right)^{10}\ge0\)
Mà theo đề bài: \(\left(\frac{1}{2}x-5\right)^{26}+\left(y^2-\frac{1}{4}\right)^{10}=0\)
=> \(\begin{cases}\left(\frac{1}{2}x-5\right)^{26}=0\\\left(y^2-\frac{1}{4}\right)^{10}=0\end{cases}\)=> \(\begin{cases}\frac{1}{2}x-5=0\\y^2-\frac{1}{4}=0\end{cases}\)=> \(\begin{cases}\frac{1}{2}x=5\\y^2=\frac{1}{4}\end{cases}\)=> \(\begin{cases}x=10\\y\in\left\{\frac{1}{2};\frac{-1}{2}\right\}\end{cases}\)
Vậy \(x=10;y\in\left\{\frac{1}{2};\frac{-1}{2}\right\}\)
a. \(2x\left(x-5\right)-x\left(2x+3\right)=26\Rightarrow2x^2-10x-2x^2-3x=26\)
\(\Rightarrow-13x=26\Rightarrow x=-2\)
b. \(\left(3y^2-y+1\right)\left(y-1\right)+y^2\left(4-3y\right)=\frac{5}{2}\)
\(\Rightarrow3y^3-3y^2-y^2+y+y-1+4y^2-3y^3=\frac{5}{2}\)\(\Rightarrow2y=\frac{7}{2}\Rightarrow y=\frac{7}{4}\)
c. \(2x^2+3\left(x+1\right)\left(x-1\right)=5x^2+5x\Rightarrow5x^2-3=5x^2+5x\)
\(\Rightarrow x=-\frac{3}{5}\)
\(26=\frac{x+\left(x-5\right)}{2}\)
\(\Leftrightarrow x+\left(x-5\right)=26\cdot2\)
\(\Leftrightarrow x+x-5=52\)
\(\Leftrightarrow2x=57\)
\(\Leftrightarrow x=\frac{57}{2}\)
\(26=\frac{x+\left(x-5\right)}{2}\)
\(\Leftrightarrow\frac{52}{2}=\frac{x+x-5}{2}\)
\(\Leftrightarrow52=x+x-5\)
\(\Leftrightarrow2x-5=52\)
\(\Leftrightarrow2x=57\)
\(\Leftrightarrow x=\frac{57}{2}=28,5\)